Agricultural Waste. (1st October 2016) - Xue, Ling; Zhang, Panpan; Shu, Huajie; Wang, Renqing; Zhang, Shuping
Abstract : In recent years, the number of agricultural waste in the world has been quickly increasing. As a result, the disadvantages and environmental problems, which are caused by agricultural waste, have aroused more and more attention. Therefore, appropriate methods must be adopted to reduce and utilize agricultural wastes. This review presented approximately 200 articles about agricultural waste published in 2015. The review introduces the study of agricultural waste published in 2015 from the following four aspects: the characterization, reuse, treatment, and management. Researchers considered it is more and more important to utilize agricultural waste and studied the potential to reuse it as biofertilizers, cultivation material, soil amendments, adsorbent material, energy recycling, enzyme and catalyst etc. The treatments of agricultural waste included carbonization, biodegradation, composting hydrolysis and pyrolysis. Moreover, this review analyzed the differences of the research progress in 2015 comparing to 2014, which may help to reveal the new findings and new trends in this field.